2018
DOI: 10.3389/fevo.2018.00126
|View full text |Cite
|
Sign up to set email alerts
|

Tomato Inoculation With the Endophytic Strain Fusarium solani K Results in Reduced Feeding Damage by the Zoophytophagous Predator Nesidiocoris tenuis

Abstract: Belowground symbiosis of plants with beneficial microbes is known to confer resistance to aboveground pests such as herbivorous arthropods and pathogens. Similarly, microbe-induced plant responses may also impact natural enemies of pests via the elicitation of plant defense responses and/or alteration of plant quality and growth. Nesidiocoris tenuis is a zoophytophagous predator and an efficient biological control agent of greenhouse pests. Its usefulness in plant protection is often hindered by its ability to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 45 publications
1
34
0
Order By: Relevance
“…We hypothesised that reduction in FsK growth may be related to the RA inhibitory effect which was produced in plants and activated resistance mechanisms in natural condition. The same results observed in tomato plants (Garantonakis et al 2018) confirmed our understanding. It is clear that all the extracts and callus showed an inhibitory effect on FsK aggregation ( Figure 6) and diameter growth (Figure 7).…”
Section: Inhibitory Effects Of In Vivo In Vitro and Callus On Fsk Grsupporting
confidence: 89%
“…We hypothesised that reduction in FsK growth may be related to the RA inhibitory effect which was produced in plants and activated resistance mechanisms in natural condition. The same results observed in tomato plants (Garantonakis et al 2018) confirmed our understanding. It is clear that all the extracts and callus showed an inhibitory effect on FsK aggregation ( Figure 6) and diameter growth (Figure 7).…”
Section: Inhibitory Effects Of In Vivo In Vitro and Callus On Fsk Grsupporting
confidence: 89%
“…A selection that reduces phytophagy in a zoophytophagous predator will result in minimizing this path by which the predator can affect their prey. In addition, plants defensive responses can be induced by an endophytic fungus, and reduce damage from both zoophytophagous predators (Garantonakis et al, 2018) and pests (Pappas et al, 2018). Garantonakis et al (2018) observed less damage from the zoophytophagous predator N. tenuis on tomato plants inoculated with the fungal endophyte Fusarium solani strain K than on uninoculated plants.…”
Section: Interactions With Host Plantsmentioning
confidence: 99%
“…In addition, plants defensive responses can be induced by an endophytic fungus, and reduce damage from both zoophytophagous predators (Garantonakis et al, 2018) and pests (Pappas et al, 2018). Garantonakis et al (2018) observed less damage from the zoophytophagous predator N. tenuis on tomato plants inoculated with the fungal endophyte Fusarium solani strain K than on uninoculated plants. The authors have not determined whether the symbiosis between the plant and the fungal endophyte confers on the plant the ability to repair damage or repel N. tenuis (reduction of phytophagy).…”
Section: Interactions With Host Plantsmentioning
confidence: 99%
“…Underlining this, Eschweiler et al studied the interaction in tomato between an endophytic, non-pathogenic strain of Fusarium oxysporum (Fo162) restricted to roots, the greenhouse whitefly Trialeurodes vaporariorum and the zoophytophagous predator M. pygmaeus. Adding to recent studies highlighting the ability of beneficial soil microbes to impact the performance and behavior of aboveground zoophytophagous mirid predators via the plant (Battaglia et al, 2013;Prieto et al, 2017;Garantonakis et al, 2018;Pappas et al, 2018), they show that tomato inoculation with Fo162 results in enhanced whitefly control, increased yield and reduced number of fruits with blossomend rot potentially providing a new preventive biological control strategy against the greenhouse whitefly.…”
Section: Interactions In Complex Food Websmentioning
confidence: 89%